Spremljanje medijev v Monoštru - Munda Hirnök, Katalin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1994)
The analysis of data on the frequency of media usage shows the role and significance of media (majority nation media, ethnic minority media, parent state media, as well as the Hungarian minority media in Prekmurje) in the information supply of the inabitants of Monošter in Porabje in Hungary. In the evaluation of results it should be taken into account that the questionnaire was performed in 1992, when individual media (mainly minority media) were still in their initial phase or did not exist at all, which is undoubtedly reflected in the answers of respondents.
Keywords: javno obveščanje; Madžarska; mediji; množični mediji; narodne manjšine; Porabje; porabski Slovenci